EFFECT OF MYOGLOBIN CONCENTRATION AS SURFACE MODIFYING MOLECULE IN ULTRAFILTRATION POLYETEHRSULFONE MEMBRANE FOR LYSOZYME SEPARATION - Ali, Nora’aini; M. T. S., Syaima; M., Mazidah (Malaysian Journal of Science, 2011)
The application of polyethersulfone (PES) as the base polymer for the fabrication of ultrafiltration (UF) and microfiltration (MF) membrane has been vastly studied for several decades. PES had been the material of choice owing to its superior selectivity, stability, good thermal and mechanical strength. However, despite the advantages, the hydrophobicity of PES still remains to be the prime constraint for the wide utilization of this polymer as the opted fabrication material for protein application since hydrophobic surfaces is known to be very susceptible to fouling. Therefore, in this study, ultrafiltration polyethersulfone (UF-PES) membrane has been modified to render the surface with hydrophilic property. The modification is done by using a simple dip coating technique, utilizing myoglobin as the coating reagent. The pH of the coating solution was fixed to pH 7.0 and the concentration of myoglobin was varied to 30, 50 and 70 mg/L. Membranes were named as MPH7-30, MPH7-50 and MPH7-70 with regard to the concentration of the myoglobin solution. To assess the hydrophilicity characteristics, these surface modified membranes were subjected to contact angle analysis. Membranes were also submitted to Attenuated Total Reflection – Fourier Transformed Infrared Spectroscopy (ATR-FTIR), Electro Kinetic Analyzer (EKA) and molecular weight cut-off (MWCO) evaluations. Membrane coated with myoglobin solution of pH 7.0 with 50 mg/L concentration (MPH7-50), shows a very remarkable characteristics and performances. Owing to this, MPH7-50 membrane was applied in the ultrafiltration of lysozyme. The stability of the membrane was also estimated from the pure water flux analysis Results showed that, MPH7-50 provides a high flux(21.95 L/m2 .h) as well as transmission (98%), thus its utilization for protein components is indeed to be promising